DEVELOPING MATHEMATICS LEARNING EQUIPMENT USING INVESTIGATION APPROACH FOR JUNIOR HIGH SCHOOL STUDENT GRADE IX AT CURVED SURFACE SOLID MATERIAL. - Nasrullah Aldiawan; Sugiyono . (Universitas Negeri Yogyakarta, 2017)
The research aim is to descript the quality of Mathematics Learning Equipment using investigation approach for junior high school student gader IX at curved surface solid material. This is a RD research using ADDIE development model which consists of five steps i.e. Analysis, Design, Development, Implementation, and Evaluation. Research instruments consist of assessment sheet (for lesson plan and student worksheet), students’ response questionnaire, and student test sheet. Implementation step in this research was held in SMP N 1 Kalikotes, Klaten. The number of lesson plan and student worksheet developed in this research is six each. The learning equipment fulfill valid criteria by assessment from validators which scoring 3,52; 3,73; 3,65 in scale of 5. 75% students pass the student test with the average score was 72,64 which means the learning equipment meets effective criteria. Students’ response questionnaire scored 4,26 average in scale of 5 which means the students worksheet fulfill very practical criteria.